2020
DOI: 10.1002/jobm.201900537
|View full text |Cite
|
Sign up to set email alerts
|

Influence of N‐acylhomoserine lactonase silver nanoparticles on the quorum sensing system of Helicobacter pylori: A potential strategy to combat biofilm formation

Abstract: The treatment of Helicobacter pylori usually fails due to their ability to form biofilms and resistance to antibiotics. This might potentially lead to gastric carcinoma and mucosa‐associated lymphoid tissue lymphoma. In the present study, we elucidate the potential role of N‐acylhomoserine lactonase stabilized silver nanoparticles (AiiA‐AgNPs) in treating biofilms produced by H. pylori. AiiA‐AgNPs inhibited quorum sensing (QS) by degradation of QS molecules, thereby reducing biofilm formation, urease productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Hence, proteins are one of the attractive targets for finding new antimicrobial therapies. To date, it has been shown that AuNPs and AgNPs, along with their respective ions, interact with several structural proteins, membrane proteins and several enzymes [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. In an experimental and molecular docking study, Shah et al evidenced the diverse action of AgNPs on various proteins of Pseudomonas aeruginosa [ 32 ].…”
Section: Interaction Of Gold and Silver Nanoparticles With Biofilmmentioning
confidence: 99%
“…Hence, proteins are one of the attractive targets for finding new antimicrobial therapies. To date, it has been shown that AuNPs and AgNPs, along with their respective ions, interact with several structural proteins, membrane proteins and several enzymes [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. In an experimental and molecular docking study, Shah et al evidenced the diverse action of AgNPs on various proteins of Pseudomonas aeruginosa [ 32 ].…”
Section: Interaction Of Gold and Silver Nanoparticles With Biofilmmentioning
confidence: 99%
“…In the vast majority of the studies, spherical silver nanoparticles were used, obtained from different extracts, having various sizes: A. priceps , 5–30 nm [ 125 ]; S. xanthocarpum , 4–18 nm [ 32 , 126 ]; T. vernicifluum , 4–20 nm [ 127 ]; C. longa [ 128 ] and A. nilotica , 22–66 nm [ 124 ]; P. putida , 6–16 nm [ 35 ]; A. calamus , 5–60 nm [ 129 ]; A. nilotica , 22–55 nm [ 130 ]. The most common effect on the bacterial colonies was inhibition of growth, which was presented in six of the papers [ 124 , 125 , 127 , 128 , 131 , 132 , 133 , 134 ], followed by activation of reactive oxygen species production [ 130 , 132 ], inactivation of H. pylori urease [ 131 , 135 ], bacterial DNA fragmentation and consecutive loss of viability [ 130 ], damage to the bacterial cellular membrane [ 132 ], and activation of antioxidant activity [ 136 ].…”
Section: The Antibacterial Mechanism Of Silver Nanoparticles: An Exte...mentioning
confidence: 99%
“…clarify that N-acyl homoserine lactonase-stabilized silver NPs inhibit quorum sensing (QS) by degradation, thereby reducing biofilm formation and improving the effect treatment. ( 55 ). Niaz prepared a nanodelivery system that is composed of a protein/polysaccharide core-shell crown.…”
Section: H Pylori and Nanomaterialsmentioning
confidence: 99%